KUANTITAS DAN KUALITAS RUANG TERBUKA HIJAU DI PERMUKIMAN PERKOTAAN - Agung Dwiyanto (Diponegoro University, 2009)
Green Air-Gap management in area of settlement urban tend to to experience of the challenge which enough weightof effect about height of urbanization current. while on the other side, energy support the downhill existing socialand environment also, so that cannot make balance to the requirement of space of effect about human pressure .Other challenge go together the height mount the conversion or displace to utilize the farm from farm (especiallyagriculture farm become the area develop;builded) generating impact to lowering environmental quality nyabecome green of urban. Evaluate the planology is exist in generally only study the aspect of accuracy or deviation ofspace according about zoning which already specified . Meanwhile its exploiting intensity change seldom debate, sothat need the new stages;steps to improve;repair the quality and existing amount green space.